Pegaruh Promo Shopee Tanggal-Tanggal Istimewa Terhadap Minat Beli Pada Followers Instagram Shopee - Christin Natalia Sianipar; Rizky Wanda Aulia (Management And Business Progress, 2025)
This study aims to determine the Impact of the Shopee Promo "Special Dates" on Purchase Interest on Shopee Instagram Followers. The research method used is a quantitative method using the help of SPSS version 25.00 which was collected from the results of distributing questionnaires to 100 respondents. The analysis method used in this study is using an instrument test, namely the validity and reliability test. The classical assumption test is the normality test, multicollinearity test, heteroscedasticity test, simple linear regression analysis, determination coefficient analysis (R2), hypothesis test is the T test. The results of SPSS in this study are that the special dates promotion variable (X) has an effect on the purchase interest variable.